A systematic analysis across North Atlantic countries unveils subtleties in cod product labelling. (July 2016) - Bréchon, Amanda L.; Hanner, Robert; Mariani, Stefano
Abstract: Over the last decade, the mislabelling of seafood products has come into prominence in the fields of food science and marine conservation. This study aims to determine whether differences in fish labelling accuracy can be explained by factors associated with governance, legislation and product availability, using cod ( Gadus spp.) as a case study. A total of 401 cod products from a range of different supermarket retailers in each of nine countries bordering the North Atlantic Ocean were purchased and genetically identified. The countries sampled were grouped into primarily cod-importing or cod-producing states, and belonging/not-belonging to the European Union. They comprised the United Kingdom, Belgium, the Netherlands, Denmark, Estonia, Iceland, Norway, Sweden and Canada. Estonia showed the highest incidence of mislabelling, with 59.4% samples mislabelled, followed by Denmark with 18.6%, Canada with 7.3%, Sweden with 4.4% and finally the United Kingdom with 2.4%. Substitute species included species within the Gadidae and Merlucciidae, such as haddock ( Melanogrammus aeglefinus ), Alaskan pollock ( Gadus chalcogrammus ) and Argentine hake ( Merluccius hubbsi ), respectively, but also included species more distantly-related to cod, such as snailfish ( Liparis spp .), spotted wolffish ( Anarhichas minor ) and yellow perch ( Perca flavescens ), the latter a freshwater species. The remaining countries showed no mislabelling. Neither EU affiliation, production nor the type of product, i.e. fresh or processed, had a significant effect on mislabelling. It is suggested that other factors, such as country-specific differences at social, cultural or legal levels, may be the greater drivers of mislabelling. Highlights: A comparative analysis of cod mislabelling across nine countries was carried out for the first time. Country's EU affiliation and/or national cod production have no significant effect on mislabelling levels. Level of mislabelling varies between 0% and nearly 60%, depending on country. The influence of social, legal and cultural factors is examined.